Consumer Behavior / Advances and Applications in Marketing - East Robert (Prentice Hall, 1997)
The book takes a questioning approach and draws strongly on published research. Preface, Introduction, Ideas and Explanations in Consumer Research, Consumer Patterns, Stationary Markets, Reasons for Purchase, Predicting and Explaining Action, Mechanisms in Coke and Consumption, Information Processing and Judgement, Applications, The Consumer as Shopper, The Response to Advertising, Bibliography, Index.